How the Paradoxical Treatment of Asian Americans as Model Minorities and Perpetual Foreigners Shape Their Burnout Experiences in Local Government. (22nd November 2022) - Le, Thai V.; Barboza-Wilkes, Cynthia
Abstract: Asian Americans are the fastest-growing racial group in the United States. This trend signals a need for greater representation and retention of Asian American employees in local government to ensure this growing population is well-represented in bureaucratic decision-making processes and public service provisions. In our study, we examine burnout and emotional labor among Asian Americans in local government through a mixed-methods approach. Our sample consists of local government workers from a large and diverse county in California. We initially surveyed over 6, 000 participants in 2018 with nearly 3, 200 fully completed and included in our statistical analyses, 16% of whom self-identified as Asian. We subsequently surveyed and interviewed a subset of 181 participants in 2020 with 7% who self-identified as Asian. We find that Asian Americans in the public sector are dealing with emotional stressors from multiple sides: internal expectations and collectivist values, external pressures from interpersonal relationships at work and from residents, and racialized collective trauma from the public display of anti-Asian acts that only heighten feelings of being perpetually foreign. The interaction of these stressors is leading Asian Americans in the public sector to experience burnout and its many dimensions in greater intensity than non-Asian employees in general.